Trajectory Planning of a 5-DOF Serial Robot Manipulator in Joint-Space - (:unkn) unknown (GAZI UNIV, 2017)
In this study, a five Degrees of Freedom (DOF) serial robot manipulator with revolute joints was designed and realized to be used for educational purposes. The robot has 150 gr payload and the motions of the joints were provided by using radio controlled R/C servo motors with smooth and vibration-free movement. In order to perform the trajectory planning in the joint space the inverse kinematics problem of the robot was solved and a third order polynomial was used for the trajectory planning. So as to present a simple and efficient way to the user for controlling the robot, a visual user interface was also designed by utilizing Visual Basic Programming Language. Finally, it was observed that the designed mechanism has been successfully used by the students for the projects involving robots.
Keywords: Manipulator; Trajectory Planning; Inverse Kinematics; Third Degree Polynomial; SIMULATION TOOLBOX; EDUCATION